Plasma-soluble marker for intraorgan regional flows - LITTLE, STEPHEN E. (1983)
Measurement of regional plasma flow is needed to quantitate the delivery of substrates and drugs to cells. For estimating regional plasma flows an ideal deposition marker should be 100% extracted during transorgan passage and retained until local tissue concentrations can be measured. To escape quickly, the tracer must penetrate capillary endothelial cells rapidly. To be retained, it must bind or be transformed or accumulated by cells. Desmethylimipramine (DMI, mol wt 266.3), a norepinephrine reuptake inhibitor, is suitable. On injection of [(3)H]DMI and (131)I-albumin simultaneously into the coronary artery inflow of isolated Ringer-perfused rabbit hearts at 37°C, extractions were >99% at plasma flows (F(s)) up to 2.3 ml·g(–1)·min(–1) and >94% with F(s) up to 5.1. Retention at F(s) < 2.3 averaged 99.0 ± 0.55% (SD, n = 6) at 0.5 min, 98.4 ± 0.5% at 1 min, and 96.6 ± 1.1% or >95% at 3 min. Retentions were similar in two dog hearts in situ. With F(s) > 3 ml·g(–1)·min(–1), there was greater escape, 4.2 ± 2.7% at 1 min and 6.8 ± 4.2% at 3 min. The fractional escape rates of loss at 2 min or more were about 1%/min at all flows, suggesting that the spatial profiles of deposition did not change thereafter. Thus DMI is nearly ideal as a “molecular microsphere.”